Estimation of the Critical Temperatures of Some More Deep Eutectic Solvents from Their Surface Tensions - Yizhak Marcus (Advances in Materials Science and Engineering)
The critical temperatures of two dozen deep eutectic solvents, for only some of which these have been estimated previously, were estimated from the temperature dependences of their surface tensions and densities available in the literature according to the Eötvös and the Guggenheim expressions.